Treatment-refractory catatonia in an adolescent with a de novo SIK1 candidate variant: a case report of a multidisciplinary diagnostic odyssey - Hodara, Emmanuelle; Seegan, Alexis; Ji, Jianling; Van Speybroeck, Alexander (Frontiers in Psychiatry, 2025)
We report the case of an adolescent patient who developed severe, treatment-refractory catatonia with progressive neurological decline over five years following a brief, self-limited acute psychotic episode following a prodromal period emerging at age 11 with disorganized behavior and restricted, stereotyped interests. Her atypical presentation marked by prolonged mutism, function loss, and retrograde amnesia, unresponsive to standard therapies, showed dramatic improvement with a combination of memantine, oxcarbazepine, and electroconvulsive therapy (ECT). Trio-clinical exome sequencing revealed a de novo likely pathogenic variant in the SIK1 gene, highlighting the utility of genomic diagnostics in complex neuropsychiatric presentations and emphasizing the ongoing need for multidisciplinary collaboration and advocacy in patient care.